IMPROVING STUDENTS’ MOTIVATION IN LEARNING ENGLISH BY USING TOTAL PHYSICAL RESPONSE (TPR) AT GRADE VI OF MI SA’ADAH EL – ISLAMIYAH TEMBILAHAN - Siti Nurina; Samsul Amri; Edi Ardian (J-Shelves of Indragiri (JSI), 2020)
The problem in this research was fewer students’ motivation in learning English. This research aimed to increase students’ motivation in learning English by using the Total Physical Response (TPR) method. This research is a Classroom Action Research (CAR). The participants in this research were twenty-five students, twelve men and thirteen women in the sixth-grade of MI Sa'adah El-Islamiayah Tembilahan. The data were collected in each cycle from observation, questionnaire, and field notes. The findings of this research showed that the study by using the Total Physical Response (TPR) method has increased the students’ motivation in learning English in the sixth-grade of MI Sa'adah El-Islamiyah Tembilahan after two cycles have done. It can be seen from the result of the questionnaire, observation, and field note. In the first cycle, it was seen that there was a slight increase to the students’ motivation in learning English while in the second cycle; the students' motivation was more increased than the first cycle. Furthermore, the researchers concluded that using the Total Physical Response (TPR) method was able to increase the students’ motivation in learning English. As a recommendation, the method can be utilized to grade up the students’ better-learning motivation.